The negative effects caused by the construction and operation of hydroelectric plants (Research, Society and Development, 2020)
Addressing issues related to ways of obtaining and transforming energy has been controversial since the beginning of these processes. There are several ways that each country works in search of increasing its energy supply. Each type of power generation requires study and causes at least some type of environmental impact, which may be more harmful or not. The objective of this work was to address energy issues in Brazil and to mention the most common impacts caused by the search for energy production, such as the flooding of large areas, relocation of families and animals in the areas to be flooded, damming of the rivers, but mainly focusing in one of the worst impacts, which is the generation of greenhouse gases in hydroelectric power plant dams and which are not accounted for in this type of enterprise. The bibliographic research technique was used for the preparation of this article, where it aims to study in depth a pre-defined question and update it in order to make the work as recent as possible, while also bringing the most important questions related to the theme in a more compact. As a conclusion, it was evident that even if not analyzed in depth, the negative effects of hydroelectric plants need to be studied with more caution so that they can be minimized. These effects also need to be put in place when choosing to build a new energy generator in detriment to another, as countries are already changing their energy matrixes in search of greater efficiency and protection of the environment.